2020
DOI: 10.1002/bdr2.1676
|View full text |Cite
|
Sign up to set email alerts
|

A novel biallelic splice‐site variant in the LRP4 gene causes sclerosteosis 2

Abstract: The LRP4 gene encodes the highly conserved low‐density lipoprotein receptor‐related protein 4 (LRP4), which acts as a co‐receptor for sclerostin. Sclerostin and LRP4 negatively regulate WNT/β‐catenin signaling pathway and lack of their inhibitory activity leads to constant osteoblastic differentiation. Consequently, increased bone formation occurs, which in the case of LRP4 mutations results in sclerosteosis type 2 (SOST2). Alterations within the LRP4 may also cause Cenani‐Lenz syndactyly syndrome (CLSS), cong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…30 Moreover, LRP4 negatively regulates the Wnt/β-catenin pathway during osteoblastic differentiation. 41 Accumulating evidence continues to demonstrate that the Wnt/β-catenin pathway can promote the proliferation and differentiation of bone cells, and bone formation, thereby facilitating fracture healing. 21,42 Thus, we reasoned that exosome-encapsulated miR-136-5p from BMSCs may promote the osteogenic proliferation and differentiation by targeting the LRP4/Wnt/β-catenin signalling axis.…”
Section: Discussionmentioning
confidence: 99%
“…30 Moreover, LRP4 negatively regulates the Wnt/β-catenin pathway during osteoblastic differentiation. 41 Accumulating evidence continues to demonstrate that the Wnt/β-catenin pathway can promote the proliferation and differentiation of bone cells, and bone formation, thereby facilitating fracture healing. 21,42 Thus, we reasoned that exosome-encapsulated miR-136-5p from BMSCs may promote the osteogenic proliferation and differentiation by targeting the LRP4/Wnt/β-catenin signalling axis.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with sclerosteosis 2 carrying heterozygous LRP4 variants, however, have also been reported. 25,26 We report five heterozygous missense mutations (p.Leu1356Arg, p.Ala1702Gly, p.Arg263His, p.Gly-1314Ser, and p.Asn1385Ser) in LRP4 in 11 patients from six unrelated Thai families affected with dental anomalies. We hypothesize that these five variants are associated with dental anomalies and are not simply coincidental findings.…”
Section: Discussionmentioning
confidence: 97%
“…However, more recently, Bukowska-Olech et al reported on a homozygous splice-site variant (c.1048 + 6 T > C), located before the β-propeller domains of LRP4, in a sclerosteosis patient. As no functional studies were performed, it is unclear whether this identified variant leads to a complete loss of function, and whether it also affects the sclerostin–LRP4 interaction [ 18 ]. In addition to the aforementioned variants in the third β-propeller domain, genetic variation spread across other regions of LRP4 is shown to cause other disorders ( Figure 1 ), such as Cenani–Lenz syndactyly syndrome (OMIM #212780), myasthenia gravis (OMIM #616304), and isolated syndactyly [ 15 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%